Dmrt1 polymorphism covaries with sex‐determination patterns in Rana temporaria. Issue 15 (30th May 2016) - Ma, Wen‐Juan; Rodrigues, Nicolas; Sermier, Roberto; Brelsford, Alan; Perrin, Nicolas
Abstract: Patterns of sex‐chromosome differentiation and gonadal development have been shown to vary among populations of Rana temporaria along a latitudinal transect in Sweden. Frogs from the northern‐boreal population of Ammarnäs displayed well‐differentiated X and Y haplotypes, early gonadal differentiation, and a perfect match between phenotypic and genotypic sex. In contrast, no differentiated Y haplotypes could be detected in the southern population of Tvedöra, where juveniles furthermore showed delayed gonadal differentiation. Here, we show that Dmrt1, a gene that plays a key role in sex determination and sexual development across all metazoans, displays significant sex differentiation in Tvedöra, with a Y‐specific haplotype distinct from Ammarnäs. The differential segment is not only much shorter in Tvedöra than in Ammarnäs, it is also less differentiated and associates with both delayed gonadal differentiation and imperfect match between phenotypic and genotypic sex. Whereas Tvedöra juveniles with a local Y haplotype tend to ultimately develop as males, those without it may nevertheless become functional XX males, but with strongly female‐biased progeny. Our findings suggest that the variance in patterns of sex determination documented in common frogs might result from a genetic polymorphism within a small genomic region that contains Dmrt1 . They also substantiate the view that recurrent convergences of sex determination toward a limited set of chromosome pairs may result from the co‐option of small genomic regions that harbor key genes from the sex‐determination pathway. Abstract : Dmrt1, a gene that plays a key role in sex determination and sexual development across all metazoans, displays significant sex differentiation in the common frog, Rana temporaria, in the North Sweden in Tvedöra with a Y‐specific haplotype distinct from Ammarnäs. It is less differentiated and associates with both delayed gonadal differentiation and imperfect match between phenotypic and genotypic sex. Our findings suggest that the variance in patterns of sex determination documented in common frogs might result from a genetic polymorphism within a small genomic region that contains Dmrt1 .